Robot imitating human skiing used for teaching and equipment testing - Lahajnar, L.; Nemec, B. (Science and Skiing IV, 2009)
The background of every well-rounded ski coach and instructor should include education in the fundamental physical mechanics and biomechanics of the sport. Because most ski coaches and instructors have little formal background in physical science, learning the physics of skiing is for them much like it is for university students who are non-science majors. Much research has been done on how such university students learn physics, and a number of demonstrably successful pedagogical techniques have arisen from it. This paper provides an overview of the pertinent education research, practical techniques that have been derived from it, and examples of their successful application to teaching the physical mechanics and biomechanics of skiing to coaches and instructors.